2021
DOI: 10.1007/s10857-021-09517-0
|View full text |Cite
|
Sign up to set email alerts
|

Australian primary school teachers’ perceived barriers to and enablers for the integration of children’s literature in mathematics teaching and learning

Abstract: This qualitative survey study set out to investigate in-service and pre-service primary school teachers’ perceived barriers to and enablers for the integration of children’s literature in mathematics teaching and learning in an Australian educational context. While research over the past three decades have documented pedagogical benefits of teaching mathematics using children’s literature, research into teachers’ perceptions regarding the use of such resources is virtually non-existent. The study thus filled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Pre-service teachers may understand the importance of practitioner competencies as they observed that a qualified integration requires a lot of effort and time, such as choosing a book and preparing a detailed lesson plan, as well as successfully implementing this plan. These findings of the study are convenient with the literature because in most of the studies, in-service and pre-service teachers both underlined the time constraint and the limited resources such as books that are appropriate for mathematics education as barriers to the integration (Can et al, 2020;Farrugia & Trakulphadetkrai, 2020;Livy et al, 2021;Prendergast et al, 2019). With this training, they could see the potential of the other children's books that are not directly linked with mathematics.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Pre-service teachers may understand the importance of practitioner competencies as they observed that a qualified integration requires a lot of effort and time, such as choosing a book and preparing a detailed lesson plan, as well as successfully implementing this plan. These findings of the study are convenient with the literature because in most of the studies, in-service and pre-service teachers both underlined the time constraint and the limited resources such as books that are appropriate for mathematics education as barriers to the integration (Can et al, 2020;Farrugia & Trakulphadetkrai, 2020;Livy et al, 2021;Prendergast et al, 2019). With this training, they could see the potential of the other children's books that are not directly linked with mathematics.…”
Section: Discussionsupporting
confidence: 62%
“…Teachers' planned behavior about the integration of children's literature and mathematics education was investigated by lots of detailed qualitative studies. In these studies, researchers found that teachers were hesitant about the benefits of this integration because of their lack of pedagogical knowledge (Farrugia & Trakulphadetkrai, 2020;Livy et al, 2021;Prendergast et al, 2019). So, with the training provided in this study, pre-service teachers may gain new insights into the integration process.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The use of children's literature or picture story books in mathematics instruction is a commonly promoted practice with a rich history over decades [28]. A recent study by Livy and colleagues [29] revealed that three-quarters of Australian in-service primary school teachers who responded to their questionnaire used children's literature to support mathematics instruction at least occasionally, with around one-third of study teachers doing so more frequently (at least once per month). Numerous books describe the ways in which stories can be used as a springboard or hook for exploring mathematical ideas [30,31].…”
Section: Using Children's Literature In Mathematics Instructionmentioning
confidence: 99%
“…This could include preservice teachers developing their own challenging tasks around familiar narrative contexts, as well as them subsequently teaching with these tasks in a practical classroom environment. This may help to address one notable barrier to teaching mathematics using narratives such as picture story books that has been noted in the literature; specifically, that some teachers lack the pedagogical knowledge, confidence and experience to feel comfortable teaching mathematics in this manner [29].…”
Section: Limitations and Implicationsmentioning
confidence: 99%